Pitfalls in Diagnosis of Early-Onset Inflammatory Bowel Disease - Dore, Mariela; Triana Junco, Paloma; Sánchez Galán, Alba; Prieto, Gerardo; Ramos, Esther; Muñoz Romo, Martha; Gómez Cervantes, Manuel; Hernández, Francisco; Martínez, Leopoldo; López Santamaría, Manuel (European Journal of Pediatric Surgery, 2018)
Aim The onset of inflammatory bowel disease (IBD) in patients younger than the age of 5 years is rare. Moreover, when there is exclusive colonic inflammation, diagnosis can be challenging. Our aim was to describe the difficulties and pitfalls in the diagnosis of early-onset IBD (eoIBD) and their repercussions in treatment decisions.Patients and Methods Patients with eoIBD (Crohn's disease [CD], ulcerative, and unclassified colitis) treated at our center between 1990 and 2016 were studied retrospectively. Demographic, clinical, medical, and surgical treatment data were analyzed.Results A total of 19 patients were diagnosed with eoIBD at 21 (1–46) months of age. Bloody diarrhea, growth failure, and abdominal pain were present in 90, 42, and 16%, respectively. After 9 (1–62) months from the onset, patients were classified as ulcerative colitis (nine), CD (two), and unclassified colitis (eight). Unresponsiveness to medical treatment was observed in 10 and prompted surgical assessment. A partial colectomy was performed in one, and nine underwent a total colectomy (one end stoma and eight ileoanal anastomosis [IAA]). At least one surgical complication occurred in 80% and ultimately six patients with an IAA required an end stoma. Overtime, final diagnosis of 5 out of the 10 surgical patients changed due to biopsy findings, unresponsiveness to medical treatment, or extraintestinal and perianal manifestations. After a 12-year (1–22) follow-up, 57.9% of the diagnoses of all patients were modified.Conclusion EoIBD poses a challenge due to ambiguous presentation and absence of specific diagnostic tests. Surgical evaluation is often needed and surgeons must be mindful of possible initial misdiagnosis, in addition to short- and long-term outcomes before deciding aggressive surgical measures as well as intestinal reconstruction.
Keywords: inflammatory bowel disease; early onset; surgical assessment; ulcerative colitis; Crohn's disease